2023
DOI: 10.1073/pnas.2214636120
|View full text |Cite
|
Sign up to set email alerts
|

Circadian ribosome profiling reveals a role for the Period2 upstream open reading frame in sleep

Arthur Millius,
Rikuhiro G. Yamada,
Hiroshi Fujishima
et al.

Abstract: Many mammalian proteins have circadian cycles of production and degradation, and many of these rhythms are altered posttranscriptionally. We used ribosome profiling to examine posttranscriptional control of circadian rhythms by quantifying RNA translation in the liver over a 24-h period from circadian-entrained mice transferred to constant darkness conditions and by comparing ribosome binding levels to protein levels for 16 circadian proteins. We observed large differences in ribosome binding levels compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Although Neurospora and Arabidopsis share similar design principles in circadian rhythms as humans and flies, the proteins involved differ significantly in both structure and conservation 3537 . Recent studies have shown that uORFs in the mouse core clock gene Period2 ( Per2 ) play a role in temperature entrainment of the circadian clock 38 and in regulating sleep 39 . However, no significant differences in the period and amplitude of circadian rhythms were observed between wild-type and Per2 uORF mutant mice 39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Neurospora and Arabidopsis share similar design principles in circadian rhythms as humans and flies, the proteins involved differ significantly in both structure and conservation 3537 . Recent studies have shown that uORFs in the mouse core clock gene Period2 ( Per2 ) play a role in temperature entrainment of the circadian clock 38 and in regulating sleep 39 . However, no significant differences in the period and amplitude of circadian rhythms were observed between wild-type and Per2 uORF mutant mice 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that uORFs in the mouse core clock gene Period2 ( Per2 ) play a role in temperature entrainment of the circadian clock 38 and in regulating sleep 39 . However, no significant differences in the period and amplitude of circadian rhythms were observed between wild-type and Per2 uORF mutant mice 39 . In addition, extensive ribosomal binding to uORFs in rhythmically expressed mRNAs has been observed in mammalian cells, yet the functional impacts of these uORFs in circadian regulation have not been characterized 40,41 .…”
Section: Introductionmentioning
confidence: 99%